Insights into selection and application of carbohydrate-based carriers for microencapsulation: Stability and functional properties of maltodextrin, gum Arabic, and β-cyclodextrin in encapsulating tea flower pollen peptides - Pegah Mehrali; Seyed Hadi Peighambardoust; Amir Akbarmehr; Khashayar Sarabandi (Carbohydrate Polymer Technologies and Applications)
Protein from tea flower pollen (TFP) was extracted and hydrolyzed to achieve polypeptides. The produced peptides were rich in hydrophobic (∼44 %), antioxidants (∼19 %), and essential (∼49 %) amino acids. Various carriers, including maltodextrin (MD), gum Arabic (GA), and β-cyclodextrin (βCD), along with their combinations, were utilized for the encapsulation purpose. The highest spray-drying yield (∼59 %) was achieved when a combination of MD-βCD was used as carrier. The physical characteristics of spray-dried (SD) powders including bulk and tapped densities (packing ability), Hassner ratio, angle of repose and Carr index (powder flowability) were influenced by the type of carriers used. The maximum solubility (88 %) and wettability (333 s) values were obtained for SD-powders produced by MD-GA as carrier. The encapsulation of peptides using MD-βCD caused a significant decrease in the hygroscopicity (from ∼85 to 39 %), indicating their higher physical stability compared to other carriers. The highest antioxidant activity in inhibiting DPPH− (∼52.1 %) and ABTS+ (∼62.5 %) radicals was obtained in peptides stabilized with MD-βCD. Morphological features of SD-powders were affected by the type of carriers. SEM showed that utilizing MD-βCD as carrier leads to formation of spherical particles with smooth surface with less pore formation. FT-IR showed the coverage of amide regions and functional groups of peptides and indicated their placement and distribution within the carrier matrix. This study highlights the potential of using microencapsulated tea flower pollen peptides as a functional ingredient for food and nutraceutical applications.